Pengaruh Kompensasi & Pelatihan Terhadap Kinerja Pegawai Yang Dimediasi Oleh Keseimbangan Kehidupan Kerja Pada Perusahaan Pengolahan Uang Rupiah - Irene Putri Jauri; Hery Winoto TJ; Melitina Tecoalu (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to analyze the effect of compensation on employee performance, the effect of training on employee performance, the effect of compensation on work-life balance, the effect of training on work-life balance, the effect of work-life balance on employee performance, the mediating effect of work-life balance on the effect of compensation on employee performance and the mediating effect of work life balance on the effect of training on employee performance. The research model used is a survey method with a quantitative approach, namely by focusing on hypothesis testing. The sample of this research is 171 employees of PT Artha Lestari. The sampling method is the Likert Scale Method.